Tales from the provinces - Devendra, Tissa (Ratmalana : Sarvodaya Vishva Lekha Publishers, 1998)
Events during the author's career as a government administrator in the provinces of Sri Lanka.
Keywords: Devendra, Tissa; Local government -- Sri Lanka; Sri Lanka -- Social life and customs